Repeated Moral Hazard - Rogerson, William P. (Econometrica, 1985)
[This paper considers a repeated principal agent relationship where the principal is risk neutral, the agent is risk averse, the principal can borrow or save at a fixed interest rate, and the agent discounts future consumption. It is shown that memory plays a very strong role in every Pareto-optimal contract. Sufficient conditions for Pareto-optimal contracts to exhibit rising or falling wages are identified. Finally, it is shown that the restriction of the agent's access to credit is necessary to achieve a Pareto-optimal outcome. In particular, under every Pareto-optimal contract for every outcome of every period the agent would choose to save some of his wage if he could.]